The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-879x2005000100002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a P2Y4-like purinoceptor triggers an increase in cytosolic [Ca2+] in the red blood cells of the lizard Ameiva ameiva (Squamata, Teiidae)

Abstract: An increasing number of pathophysiological roles for purinoceptors are emerging, some of which have therapeutic potential. Erythrocytes are an important source of purines, which can be released under physiological and physiopathological conditions, acting on purinergic receptors associated with the same cell or with neighboring cells. Few studies have been conducted on lizards, and have been limited to ATP agonist itself. We have previously shown that the red blood cells (RBCs) of the lizard Ameiva ameiva stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…2001). A later study suggested that this was a P2Y 4 ‐like receptor as UTP was a potent agonist (Sartorello & Garcia 2005). Activation of this receptor resulted in InsP 3 production and Ca 2+ mobilization from the ER.…”
Section: Lower Vertebratesmentioning
confidence: 99%
“…2001). A later study suggested that this was a P2Y 4 ‐like receptor as UTP was a potent agonist (Sartorello & Garcia 2005). Activation of this receptor resulted in InsP 3 production and Ca 2+ mobilization from the ER.…”
Section: Lower Vertebratesmentioning
confidence: 99%
“…Present in the immature stage of mammalian erythrocytes, birds, amphibians, fishes and reptiles, nucleated RBCs differ from mature mammalian erythrocytes by the presence of a nucleus and organelles. Despite this, few studies of the mechanisms of Ca 2+ homeostasis in nucleated RBCs have been performed [ 15 , 16 ]. By studying signal transduction pathways in lizard RBCs from different families, we have been able to infer phylogenetic aspects and mechanisms for these cells to maintain its Ca 2+ homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence shows that the increase in calcium concentration was not due to ionic influx, discarding the possibility for these cells to display P2X purinoceptors (Beraldo et al, 2001). In A. ameiva RBCs, a pharmacological characterization of the purinoceptor, evidenced a P2Y 4 -like receptor, since UTP, UDP, GTP, ATPγS evoked a dose-dependent calcium response, and 2MeSATP, 2ClATP, α,β-ATP and ADP failed to promote a elevation in [Ca 2+ ] i (Sartorello and Garcia, 2005).…”
Section: Purinoceptors: Perceiving Extracellular Messagesmentioning
confidence: 98%